Video Enhanced RFID Tracking System - Nafiz ARICA; Anil CELIK; Bayazit KARAMAN; Coskun BAYRAK; Onur KECECI (International Journal of Applied Methods in Electronics and Computers, 2015)
Generally speaking, crimes in which vehicles are used are generally highly organized criminal activities affecting all regions of the world and with clear links to illegal activities and terrorism [3]. Therefore, catching illegal vehicles on the roads is an important preventive measure in security. In this paper, we propose a Video Enhanced RFID Tracking System to monitor the activities of vehicles through the use of readers, tags, and video together. The proposed system retrieves the registered visual properties of vehicles in the environment by querying their RFID tags on the database in the Command Control Center. It processes the video frames simultaneously, and extracts the visual features of detected vehicles. The information collected both from video and RFID database query is then combined in such a way that they validate each other. If an inconsistency is detected in this process an existence of illegal vehicle is found in the environment.